MENINGKATKAN KEMAMPUAN BAHASA DAN KETERAMPILAN BERNYANYI BAHASA INGGRIS BAGI MUDA MUDI GEREJA HKBP MARTUBUNG: Improving Language Ability And English Singing Skills For Youth Of Hkbp Martubung Church - Rony Arahta Sembiring; Kamaluddin Galingging; Jubilezer Sihite; Dewi Sartika Sitompul; Sari Febriyanti Situmorang; Yoan Novri Yanti Japardi (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The ability to speak English in today's digital era has become a must for everyone to be able to survive in global competition. For this reason, the team from the Faculty of Languages and Arts, University of HKBP Nommensen Medan, provided training to the young people of the HKBP Martubung church to develop their English language skills and their application in singing techniques. In this training, the method used is interactive question-and-answer discussions and lectures to increase the motivation and participation of participants in each activity. Based on the results of the learning evaluation obtained by the Language and Arts Faculty team, there was a good change and an increase from the first month of training to the end of this activity. All participants were very enthusiastic about showing their ability to sing in English, although there were still some children who seemed reluctant to show their abilities in singing. Given the limited time available, it is hoped that the intensity of training like this can be carried out regularly so that the motivation and desire to learn among young people can continue to be developed in order to gain better skills.